Method for forming multilayer coating film
The method addresses the issue of insufficient metallic gloss and uneven finishes in multi-layer coating films by using a sequential coating and curing process with specific resin particles and pigment dispersions, resulting in a high-quality, aesthetically pleasing finish on plastic molded products.
Patent Information
- Application Number
- JP2023180591
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-05-02
AI Technical Summary
Existing methods for forming multi-layer coating films on plastic molded products often result in coatings with insufficient metallic gloss and uneven finishes, which affect the aesthetic and commercial properties of the final product.
A method involving sequential coating steps: an aqueous primer paint, a preheated base paint, a bright pigment dispersion, and a clear paint, all of which are then cured simultaneously at a temperature between 110 to 130°C. The aqueous base paint includes hydroxyl group-containing acrylic resin particles with specific acid values, and the bright pigment dispersion contains flaky aluminum pigments and cellulose viscosity adjusters, achieving a solid content of 2 to 6% by mass.
This method produces a multi-layer coating film with excellent finish appearance and brightness, ensuring a well-finished and highly designed surface on plastic molded products, while also allowing for low-temperature baking of bumpers.
Smart Images

Figure 2025070349000001 
Figure 2025070349000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for forming a multi-layer coating film. [Background technology]
[0002] In general, coating films formed by applying paint to various substrates are required to protect the substrates and to impart design (beauty) to their appearance. In particular, topcoat paints applied to the exterior panels and bumpers of automobiles are required to form topcoat films with high texture and design.
[0003] For example, a multi-layer coating film of metallic paint color, which has become mainstream in recent years as a topcoat coating film with a high-class design, is formed using a topcoat paint that contains a glittering base paint containing a glittering pigment to obtain high glittering, and a transparent clear paint. A highly glittering coating film is a coating film that has high gloss, and further, the glittering pigment is relatively uniformly distributed in the coating film, and metallic unevenness is hardly observed.
[0004] Usually, aluminum flake pigments with metallic luster are used for the glitter pigments. In general, multi-layer coatings of these metallic coatings are formed by successively coating a base coating, a glitter base coating containing the glitter pigment, and a clear coating on the substrate in a wet-on-wet manner, and then curing the resulting uncured coating in a single baking process.
[0005] For example, Patent Document 1 describes a method for forming a metallic luster coating film, which is characterized by sequentially coating and curing a first base metallic paint, a second base luster paint containing a fine scale-like pigment or a fine scale-like pigment and an aluminum pigment (C), and a clear paint, the first base metallic paint including (A) an aluminum pigment having an average particle diameter D50 of 13 to 40 μm and an average thickness of 0.4 to 2.5 μm and (B) an aluminum pigment having an average particle diameter D50 of 4 to 30 μm and an average thickness of less than 0.02 to 0.4 μm, the solid content mass ratio (A / B) of the aluminum pigments (A) and (B) being 90 / 10 to 10 / 90, and the total solid content mass (A+B) of the aluminum pigments (A) and (B) being 5 to 50 parts by mass per 100 parts by mass of resin solid content, and the first base metallic paint, a fine scale-like pigment, or a fine scale-like pigment and an aluminum pigment (C), and a clear paint, the first base metallic paint being 5 to 50 parts by mass per 100 parts by mass of resin solid content, the second base metallic paint being 5 to 50 parts by mass, and the clear paint being 5 to 50 parts by mass. The first base metallic paint is excellent in hiding power and has a luster that combines a high level of pearl luster and metallic luster, and a three-dimensional luster.
[0006] However, in the method described in Patent Document 1, the coating film formed by the second base luster paint is relatively thick and has insufficient metallic luster.
[0007] Patent Document 2 describes the following steps (1) to (5): (1) a step of applying a colored coating material (W) onto an object to be coated and heating the applied material to form a colored coating film; (2) a step of applying a base coating material (X) onto the colored coating film formed in step (1) to form a base coating film; (3) a step of applying a glittering pigment dispersion (Y) onto the base coating film formed in step (2) to form a glittering coating film; (4) a step of applying a clear coating material (Z) onto the glittering coating film formed in step (3) to form a clear coating film; and (5) a step of applying steps (2) to (4) to (6) to (8) to (9) to (10). (4) A method for forming a multilayer coating film by sequentially carrying out a step of heating the uncured base coating film, the uncured glittering coating film, and the uncured clear coating film formed in step (3) to simultaneously cure these three coating films, in which the glittering pigment dispersion (Y) contains water, a surface conditioner (A), a scaly glittering pigment (B), and a viscosity conditioner (C), and the solids content is 0.5 to 10 mass %, and it is described that this method for forming a multilayer coating film can provide a multilayer coating film that exhibits an excellent metallic luster.
[0008] The method described in Patent Document 2 can obtain an excellent metallic luster, but may cause sagging due to the low solid content of the bright pigment dispersion (Y).
[0009] Furthermore, in fields such as automobile painting, the finish of the coating film formed has a significant impact on its marketability, so it is necessary to develop a coating film formation method that can form a multi-layer coating film with a good finish and high design quality.
[0010] Furthermore, unlike exterior panels, bumpers, which are made from molded plastics, require baking at a relatively low temperature to harden the paint film. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2008-237939 A [Patent Document 2] International Publication WO2018 / 092874 Summary of the Invention [Problem to be solved by the invention]
[0012] An object of the present invention is to provide a method for forming a multi-layer coating film which can provide a multi-layer coating film having excellent finish appearance and luster on a plastic molded article. [Means for solving the problem]
[0013] The present invention includes subject matter described in the following paragraphs.
[0014] Item 1. Step (1): A step of applying a water-based primer paint (W) onto a plastic molded product to form an uncured primer coating film; Step (2): A preheating step of preheating the uncured primer coating film; Step (3): A step of applying a water-based base paint (X) onto the preheat-treated primer coating film to form an uncured base coating film; Step (4): A step of applying a glittering pigment dispersion (Y) onto the uncured base coating film to form an uncured glittering coating film; Step (5): A preheating step of preheating the uncured base coating film and the uncured glossy coating film; Step (6): A step of applying a clear coating material (Z) onto the preheat-treated glossy coating film to form an uncured clear coating film; Step (7): A step of heating the preheat-treated primer coating film, base coating film, and glitter coating film, and the uncured clear coating film at a temperature in the range of 110 to 130°C to simultaneously cure them, in a multilayer coating film forming method, The water-based base coating material (X) comprises hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g, hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g, and an associative thickener (X3), a content ratio of the hydroxyl-containing acrylic resin particles (X1) and the hydroxyl-containing acrylic resin particles (X2) is 70 / 30 to 30 / 70 in terms of a mass ratio of the hydroxyl-containing acrylic resin particles (X1) / the hydroxyl-containing acrylic resin particles (X2); the brilliant pigment dispersion (Y) contains a scaly aluminum pigment (Y1), a cellulose-based viscosity modifier (Y2), a surface modifier (Y3) and water, and has a solid content in the range of 2 to 6 mass %, The method for forming a multilayer coating film, wherein the glossy coating film has a thickness of 0.5 to 1.5 μm after curing. Effect of the Invention
[0015] According to the present invention, there can be provided a method for forming a multi-layer coating film, which can provide a multi-layer coating film having excellent finish appearance and luster on a plastic molded product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The method for forming a multilayer coating film of the present invention comprises the steps of: Step (1): A step of applying a water-based primer paint (W) onto a plastic molded product to form an uncured primer coating film; Step (2): A preheating step of preheating the uncured primer coating film; Step (3): A step of applying a water-based base paint (X) onto the preheat-treated primer coating film to form an uncured base coating film; Step (4): A step of applying a glittering pigment dispersion (Y) onto the uncured base coating film to form an uncured glittering coating film; Step (5): A preheating step of preheating the uncured base coating film and the uncured glossy coating film; Step (6): A step of applying a clear coating material (Z) onto the preheat-treated glossy coating film to form an uncured clear coating film; Step (7): A step of heating the preheat-treated primer coating film, base coating film, and glitter coating film, and the uncured clear coating film at a temperature in the range of 110 to 130°C to simultaneously cure them, in a multilayer coating film forming method, The water-based base coating material (X) comprises hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g, hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g, and an associative thickener (X3), a content ratio of the hydroxyl-containing acrylic resin particles (X1) and the hydroxyl-containing acrylic resin particles (X2) is 70 / 30 to 30 / 70 in terms of a mass ratio of the hydroxyl-containing acrylic resin particles (X1) / the hydroxyl-containing acrylic resin particles (X2); the brilliant pigment dispersion (Y) contains a scaly aluminum pigment (Y1), a cellulose-based viscosity modifier (Y2), a surface modifier (Y3) and water, and has a solid content in the range of 2 to 6 mass %, In the method for forming a multilayer coating film, the glossy coating film has a thickness of 0.5 to 1.5 μm after curing.
[0017] Process (1) Step (1) of the present invention is a step of applying a water-based primer coating (W) onto a plastic molded article to form an uncured primer coating film. [Plastic molded products] As the material for the plastic molded product, for example, polyolefin obtained by polymerizing at least one olefin having 2 to 10 carbon atoms, such as ethylene, propylene, butylene, hexene, etc., is particularly suitable, but is not limited thereto, and polycarbonate, ABS resin, urethane resin, nylon, etc. may also be used.
[0018] The plastic molded product can be obtained, for example, by molding the above-mentioned material by a known method such as injection molding. The plastic molded product can be appropriately degreased, washed, or the like in advance by a known method. [Water-based primer paint (W)] In this specification, "water-based primer coating material (W)" refers to a water-based coating material used for the purpose of imparting adhesion to a coating material to be laminated on a plastic molded product.
[0019] The aqueous primer coating material (W) used in this step is an aqueous coating material commonly used in the art, and is preferably an aqueous coating material containing a base resin, a curing agent, an organic solvent, and water.
[0020] The above-mentioned base resin and curing agent may be known compounds commonly used in the art. Examples of the base resin include acrylic resin, polyester resin, polyurethane resin, olefin resin, etc. Examples of the curing agent include amino resin, polyisocyanate compound, blocked polyisocyanate compound, etc.
[0021] Examples of organic solvents include aliphatic hydrocarbons such as hexane and heptane, aromatic hydrocarbons such as xylene and toluene, and alicyclic hydrocarbons; esters such as ethyl acetate and butyl acetate; ethers such as ethylene glycol monomethyl ether; alcohols such as ethanol, propanol, and 2-ethylhexyl alcohol; ketones such as methyl ethyl ketone and methyl isobutyl ketone; and amides. Examples of organic solvents containing aromatic hydrocarbons include Swazol 310 and Swazol 1000 (manufactured by Cosmo Oil Co., Ltd.).
[0022] The water-based primer coating material (W) used in the method of the present invention may contain, in addition to the above-mentioned components, an ultraviolet absorber, an antifoaming agent, a thickener, an anti-rust agent, a surface conditioner, a pigment, etc., as desired.
[0023] The coating method of the water-based primer coating material (W) can be a normal coating method commonly used in the art. For example, the coating method can be a coating method using a brush or a coating machine. Among them, the coating method using a coating machine is preferred. For example, the coating machine is preferably an airless spray coating machine, an air spray coating machine, or a rotary atomizing coating machine such as a paint cassette type, and the rotary atomizing coating machine is particularly preferred. By using the above coating material and coating method, an uncured primer coating film having a good coating appearance can be obtained.
[0024] The thickness of the primer coating is preferably 5 to 20 μm, particularly preferably 7 to 15 μm, in terms of the cured thickness.
[0025] Process (2) Step (2) of the present invention is a preheating step of subjecting the uncured primer coating film to a preheat treatment.
[0026] In this specification, "preheat treatment" means a treatment in which an article having a coating film formed on its surface is heated under time and temperature conditions in which the base resin and curing agent contained in the coating film do not react or cure or do not substantially react or cure, thereby volatilizing the aqueous medium and / or other volatile substances contained in the coating film.
[0027] The temperature for the preheating treatment is preferably within a range of 40 to 80° C., and more preferably within a range of 50 to 70° C. The time for the preheating treatment is preferably 1 to 5 minutes.
[0028] Process (3) Step (3) of the present invention is a step of applying a water-based base paint (X) onto the above preheat-treated primer coating film to form an uncured base coating film. [Water-based paint (X)] In this specification, "water-based base paint (X)" means a water-based paint that is used to hide the underlying primer and improve the finished appearance.
[0029] The water-based base coating material (X) comprises hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g, hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g, and an associative thickener (X3), and the content ratio of the hydroxyl-containing acrylic resin particles (X1) and the hydroxyl-containing acrylic resin particles (X2) is 70 / 30 to 30 / 70 in terms of the mass ratio of the hydroxyl-containing acrylic resin particles (X1) / the hydroxyl-containing acrylic resin particles (X2).
[0030] From the viewpoint of the finished appearance of the resulting coating film, the mass ratio of the hydroxyl-containing acrylic resin particles (X1) / the hydroxyl-containing acrylic resin particles (X2) is more preferably 65 / 35 to 35 / 65, and even more preferably 60 / 40 to 40 / 60.
[0031] In the present invention, the "shell portion" of the "hydroxyl-containing acrylic resin particles having a core-shell structure" means the polymer layer present in the outermost layer of the resin particle, the "core portion" means the polymer layer in the inner layer of the resin particle excluding the shell portion, and "having a core-shell structure" means a structure having the core portion and the shell portion. The core-shell structure is generally a layer structure in which the core portion is completely covered by the shell portion, but depending on the mass ratio of the core portion to the shell portion, the amount of monomer in the shell portion may be insufficient to form a layer structure. In such a case, it is not necessary to have a complete layer structure as described above, and a structure in which the shell portion covers a part of the core portion may be used.
[0032] The hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90-100 mgKOH / g are acrylic resin particles consisting of a core portion which is a copolymer (I) containing a polymerizable unsaturated monomer as a copolymerization component, and a shell portion which is a copolymer (II) containing a polymerizable unsaturated monomer as a copolymerization component. The acid value of the shell can be calculated from the monomer composition.
[0033] As the above polymerizable unsaturated monomer, a hydroxyl group-containing polymerizable unsaturated monomer, an acid group-containing polymerizable unsaturated monomer and other copolymerizable polymerizable unsaturated monomers can be used in appropriate combination.
[0034] The hydroxyl-containing polymerizable unsaturated monomer is a compound having one or more hydroxyl groups and one or more polymerizable unsaturated bonds in one molecule. Examples of the hydroxyl-containing polymerizable unsaturated monomer include monoesters of (meth)acrylic acid and dihydric alcohols having 2 to 8 carbon atoms, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; ε-caprolactone-modified monoesters of (meth)acrylic acid and dihydric alcohols having 2 to 8 carbon atoms; N-hydroxymethyl (meth)acrylamide; allyl alcohol; and (meth)acrylates having polyoxyethylene chains whose molecular terminals are hydroxyl groups. However, in the present invention, monomers corresponding to the polymerizable unsaturated monomer having an ultraviolet absorbing functional group (xiv) described later should be defined as other polymerizable unsaturated monomers copolymerizable with the above-mentioned hydroxyl group-containing polymerizable unsaturated monomer, and are excluded from the hydroxyl group-containing polymerizable unsaturated monomer. These can be used alone or in combination of two or more kinds.
[0035] The acid group-containing polymerizable unsaturated monomer is a compound having one or more acid groups and one or more polymerizable unsaturated bonds in one molecule. Examples of the acid group include a carboxylic acid group, a phosphoric acid group, and a sulfonic acid group, and among these, a carboxylic acid group is preferable.
[0036] Examples of the compound having one or more carboxylic acid groups and one or more polymerizable unsaturated bonds include acrylic acid, methacrylic acid, crotonic acid, itaconic acid, maleic acid, and maleic anhydride.
[0037] Examples of the compound having one or more phosphoric acid groups and one or more polymerizable unsaturated bonds include acid phosphooxyethyl (meth)acrylate, acid phosphooxypropyl (meth)acrylate, acid phosphooxypoly(oxyethylene)glycol (meth)acrylate, and acid phosphooxypoly(oxypropylene)glycol (meth)acrylate.
[0038] Examples of the compound having one or more sulfonic acid groups and one or more polymerizable unsaturated bonds include 2-acrylamido-2-methylpropanesulfonic acid, 2-sulfoethyl (meth)acrylate, allylsulfonic acid, 4-styrenesulfonic acid, and the sodium salts and ammonium salts of these sulfonic acids.
[0039] As the other copolymerizable polymerizable unsaturated monomers, for example, the following monomers (i) to (xvii) can be used. These polymerizable unsaturated monomers can be used alone or in combination of two or more kinds. (i) Alkyl or cycloalkyl (meth)acrylates: for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, tridecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, tricyclodecanyl (meth)acrylate, and the like. (ii) Polymerizable unsaturated monomers having an isobornyl group: isobornyl (meth)acrylate, etc. (iii) Polymerizable unsaturated monomers having an adamantyl group: adamantyl (meth)acrylate, etc. (iv) Polymerizable unsaturated monomers having a tricyclodecenyl group: tricyclodecenyl (meth)acrylate, etc. (v) Aromatic ring-containing polymerizable unsaturated monomers: benzyl (meth)acrylate, styrene, α-methylstyrene, vinyltoluene, and the like. (vi) Polymerizable unsaturated monomers having an alkoxysilyl group: vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, γ-(meth)acryloyloxypropyltrimethoxysilane, γ-(meth)acryloyloxypropyltriethoxysilane, and the like. (vii) Polymerizable unsaturated monomers having a fluorinated alkyl group: perfluoroalkyl (meth)acrylates such as perfluorobutylethyl (meth)acrylate and perfluorooctylethyl (meth)acrylate; fluoroolefins, and the like. (viii) Polymerizable unsaturated monomers having a photopolymerizable functional group such as a maleimide group. (ix) Vinyl compounds: N-vinylpyrrolidone, ethylene, butadiene, chloroprene, vinyl propionate, vinyl acetate, etc. (x) Nitrogen-containing polymerizable unsaturated monomers: (meth)acrylonitrile, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, methylene bis(meth)acrylamide, ethylene bis(meth)acrylamide, adducts of glycidyl (meth)acrylate and amine compounds, and the like. (xi) Polymerizable unsaturated monomers having two or more polymerizable unsaturated groups in one molecule: allyl (meth)acrylate, ethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, etc. (xii) Epoxy group-containing polymerizable unsaturated monomers: glycidyl (meth)acrylate, β-methylglycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 3,4-epoxycyclohexylethyl (meth)acrylate, 3,4-epoxycyclohexylpropyl (meth)acrylate, allyl glycidyl ether, and the like. (xiii) (meth)acrylates having a polyoxyethylene chain whose molecular terminal is an alkoxy group. (xiv) Polymerizable unsaturated monomers having an ultraviolet absorbing functional group: 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, 2-hydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, and the like. (xv) Light-stable polymerizable unsaturated monomers: 4-(meth)acryloyloxy-1,2,2,6,6-pentamethylpiperidine, 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 4-crotonoyloxy-2,2,6,6-tetramethylpiperidine, 4-crotonoylamino-2,2,6,6-tetramethylpiperidine, 1-crotonoyl-4-crotonoyloxy-2,2,6,6-tetramethylpiperidine, and the like. (xvi) Polymerizable unsaturated monomers having a carbonyl group: acrolein, diacetone acrylamide, diacetone methacrylamide, acetoacetoxyethyl methacrylate, formylstyrol, vinyl alkyl ketones having 4 to 7 carbon atoms (for example, vinyl methyl ketone, vinyl ethyl ketone, vinyl butyl ketone), and the like. (xvii) Polymerizable unsaturated monomers having an acid anhydride group: maleic anhydride, itaconic anhydride, citraconic anhydride, and the like.
[0040] In this specification, the polymerizable unsaturated group refers to an unsaturated group capable of undergoing radical polymerization. Examples of such polymerizable unsaturated groups include vinyl groups and (meth)acryloyl groups.
[0041] In addition, in this specification, "(meth)acrylate" means acrylate or methacrylate. "(meth)acrylic acid" means acrylic acid or methacrylic acid. "(meth)acryloyl" means acryloyl or methacryloyl. "(meth)acrylamide" means acrylamide or methacrylamide.
[0042] In a typical embodiment, in order to produce the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with an acid value of the shell of 90 to 100 mgKOH / g, first, an emulsion of the core copolymer (I) is prepared by emulsion polymerization of a polymerizable unsaturated monomer mixture.
[0043] The emulsion polymerization for preparing the emulsion of the core copolymer (I) can be carried out by a conventionally known method, for example, by emulsion polymerization of a polymerizable unsaturated monomer mixture using a polymerization initiator in the presence of an emulsifier.
[0044] As the emulsifier, anionic emulsifiers and nonionic emulsifiers can be suitably used.
[0045] Examples of the anionic emulsifier include sodium salts and ammonium salts of alkylsulfonic acid, alkylbenzenesulfonic acid, alkylphosphoric acid, etc. Examples of the nonionic emulsifier include polyoxyethylene oleyl ether, polyoxyethylene stearyl ether, polyoxyethylene lauryl ether, polyoxyethylene tridecyl ether, polyoxyethylene phenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene monooleate, sorbitan monolaurate, sorbitan monostearate, sorbitan trioleate, polyoxyethylene sorbitan monolaurate, etc.
[0046] Also usable are polyoxyalkylene group-containing anionic emulsifiers having an anionic group and a polyoxyalkylene group such as a polyoxyethylene group or a polyoxypropylene group in one molecule; reactive anionic emulsifiers having an anionic group and a radically polymerizable unsaturated group in one molecule; and the like.
[0047] Examples of the reactive anionic emulsifier include sodium salts of sulfonic acid compounds having a radically polymerizable unsaturated group such as an allyl group, a methallyl group, a (meth)acryloyl group, a propenyl group, or a butenyl group, and ammonium salts of the sulfonic acid compounds.
[0048] The amount of the emulsifier used is preferably about 0.1 to 15 mass %, particularly preferably about 0.5 to 10 mass %, and even more particularly preferably about 1 to 5 mass %, based on the total amount of all monomers used in preparing the core copolymer.
[0049] Examples of the polymerization initiator include organic peroxides such as benzoyl peroxide, octanoyl peroxide, lauroyl peroxide, stearoyl peroxide, cumene hydroperoxide, tert-butyl peroxide, tert-butyl peroxy laurate, tert-butyl peroxy isopropyl carbonate, tert-butyl peroxy acetate, and diisopropylbenzene hydroperoxide; azobisisobutyronitrile, azobis(2,4-dimethyl)benzene Examples of the polymerization initiator include azo compounds such as azobis(2-methylpropiononitrile), azobis(2-methylbutyronitrile), 4,4'-azobis(4-cyanobutanoic acid), dimethylazobis(2-methylpropionate), azobis[2-methyl-N-(2-hydroxyethyl)-propionamide], and azobis{2-methyl-N-[2-(1-hydroxybutyl)]-propionamide}; and persulfates such as potassium persulfate, ammonium persulfate, and sodium persulfate. These polymerization initiators can be used alone or in combination of two or more. In addition, the above polymerization initiators can be used in combination with reducing agents such as sugars, sodium formaldehyde sulfoxylate, and iron complexes, as necessary, to form redox initiators.
[0050] The amount of the polymerization initiator is generally about 0.1 to 5% by mass, and particularly about 0.2 to 3% by mass, based on the total amount of all monomers used in the preparation of the core copolymer. The method of adding the polymerization initiator is not particularly limited and can be appropriately selected depending on the type and amount. For example, the polymerization initiator can be previously contained in the monomer mixture or aqueous medium, or can be added in one lump during polymerization, or can be added dropwise.
[0051] As the above-mentioned polymerizable unsaturated monomer, the above-mentioned polymerizable unsaturated monomer having two or more polymerizable unsaturated groups in one molecule can be used to give a copolymer crosslinked structure.When using the polymerizable unsaturated monomer having two or more polymerizable unsaturated groups in one molecule, its usage ratio can be appropriately determined according to the degree of crosslinking of the copolymer, but it is usually preferably within the range of about 0.1 to 30 mass%, particularly about 0.5 to 10 mass%, and more particularly about 1 to 7 mass% based on the total amount of the above-mentioned polymerizable unsaturated monomer used to prepare the core copolymer.
[0052] The hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with the shell having an acid value of 90 to 100 mgKOH / g can be obtained by further forming a shell copolymer (II).
[0053] The monomer mixture for forming the shell copolymer (II) may contain, as necessary, the polymerization initiator, chain transfer agent, reducing agent, emulsifier, and other components. The monomer mixture may be dropped as is, but it is preferable to drop the monomer mixture as a monomer emulsion obtained by dispersing the monomer mixture in an aqueous medium. In this case, the particle size of the monomer emulsion is not particularly limited.
[0054] An example of a method for polymerizing the monomer mixture for forming the shell copolymer (II) is to add the monomer mixture or an emulsion thereof, either dropwise in one go or dropwise slowly, to the emulsion of the core copolymer (I) and then heat to an appropriate temperature while stirring.
[0055] The hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g preferably have a hydroxyl value in the range of 1 to 50 mgKOH / g, more preferably in the range of 2 to 30 mgKOH / g, and even more preferably in the range of 3 to 20 mgKOH / g, from the viewpoint of the finished appearance of the resulting coating film.
[0056] The core of the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g preferably has a hydroxyl value of 20 mgKOH / g or less, more preferably 15 mgKOH / g or less, and even more preferably 10 mgKOH / g or less, from the viewpoint of the water resistance of the resulting coating film.
[0057] The shell portion of the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g preferably has a hydroxyl value in the range of 20 to 80 mgKOH / g, more preferably in the range of 25 to 70 mgKOH / g, and even more preferably in the range of 30 to 60 mgKOH / g, from the viewpoint of the water resistance of the resulting coating film.
[0058] The hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g preferably have an acid value in the range of 5 to 50 mgKOH / g, more preferably in the range of 10 to 40 mgKOH / g, and even more preferably in the range of 15 to 30 mgKOH / g, from the viewpoints of storage stability of the coating material and water resistance of the resulting coating film.
[0059] The core of the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g preferably has an acid value of 20 mgKOH / g or less, more preferably 15 mgKOH / g or less, and even more preferably 10 mgKOH / g or less, from the viewpoints of production stability, storage stability of the coating material, and the like.
[0060] The hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g preferably have a glass transition temperature of 20°C or higher, more preferably 30°C or higher, and even more preferably within the range of 30 to 60°C, from the viewpoint of the water resistance of the resulting coating film.
[0061] The core of the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g has a glass transition temperature of preferably 20° C. or higher, more preferably 30° C. or higher, and even more preferably within the range of 30 to 60° C., from the viewpoints of the water resistance and film-forming properties of the resulting coating film.
[0062] The shell portion of the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g has a glass transition temperature of preferably 0°C or higher, more preferably 5°C or higher, and even more preferably within the range of 5 to 30°C, from the viewpoint of the film-forming properties of the resulting coating film.
[0063] In this specification, the glass transition temperature Tg is a value calculated by the following formula. 1 / Tg(K)=W1 / T1+W2 / T2+...Wn / Tn Tg(℃)=Tg(K)-273 In the formula, W1, W2, ...Wn are the mass fractions of each monomer, and T1, T2...Tn are the glass transition temperatures Tg (K) of the homopolymers of each monomer. The glass transition temperature of the homopolymer of each monomer is a value taken from POLYMER HANDBOOK Fourth Edition, edited by J. Brandrup, Eh Immergut, and EA Grulke (1999). For the glass transition temperature of a monomer not described in the document, a homopolymer of the monomer is synthesized so as to have a weight-average molecular weight of about 50,000, and the glass transition temperature is measured by differential scanning calorimetry.
[0064] The content of the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g in the water-based base coating material (X) is preferably 2 to 70 mass%, more preferably 5 to 50 mass%, and even more preferably 10 to 40 mass%, based on the resin solid content in the water-based base coating material (X).
[0065] The hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g can be produced in the same manner as the hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g.
[0066] The hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g preferably have a hydroxyl value in the range of 1 to 50 mgKOH / g, more preferably in the range of 2 to 30 mgKOH / g, and even more preferably in the range of 3 to 20 mgKOH / g, from the viewpoint of the finished appearance of the resulting coating film.
[0067] The core portion of the hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g preferably has a hydroxyl value of 20 mgKOH / g or less, more preferably 15 mgKOH / g or less, and even more preferably 10 mgKOH / g or less, from the viewpoint of the water resistance of the resulting coating film.
[0068] The shell portion of the hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g preferably has a hydroxyl value in the range of 20 to 80 mgKOH / g, more preferably in the range of 25 to 70 mgKOH / g, and even more preferably in the range of 30 to 60 mgKOH / g, from the viewpoint of the water resistance of the resulting coating film.
[0069] The hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g preferably have an acid value in the range of 5 to 50 mgKOH / g, more preferably in the range of 10 to 40 mgKOH / g, and even more preferably in the range of 15 to 30 mgKOH / g, from the viewpoints of storage stability of the coating material and water resistance of the resulting coating film.
[0070] The core of the hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g preferably has an acid value of 20 mgKOH / g or less, more preferably 15 mgKOH / g or less, and even more preferably 10 mgKOH / g or less, from the viewpoints of production stability, storage stability of the coating material, and the like.
[0071] The hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g preferably have a glass transition temperature of 10°C or higher, more preferably 20°C or higher, and even more preferably within the range of 20 to 50°C, from the viewpoint of the water resistance of the resulting coating film.
[0072] The core of the hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g preferably has a glass transition temperature of 10°C or higher, more preferably 20°C or higher, and even more preferably within the range of 20 to 50°C, from the viewpoints of the water resistance and film-forming properties of the resulting coating film.
[0073] The shell portion of the hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g has a glass transition temperature of preferably 20°C or higher, more preferably 30°C or higher, and even more preferably within the range of 30 to 60°C, from the viewpoint of the film-forming properties of the resulting coating film.
[0074] The content of the hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g in the water-based base coating material (X) is preferably 2 to 70 mass%, more preferably 5 to 50 mass%, and even more preferably 10 to 40 mass%, based on the resin solid content in the water-based base coating material (X).
[0075] The associative thickener (X3) has a hydrophilic portion and a hydrophobic portion in one molecule, and in an aqueous medium, the hydrophobic portion is adsorbed to the surface of a resin particle or a pigment in the paint, or the hydrophobic portions are associated with each other, thereby effectively exhibiting a thickening effect.
[0076] Commercially available products can be used as the associative thickener (X3). Examples of commercially available product names include "UH-420", "UH-450", "UH-462", "UH-472", "UH-540", "UH-752", "UH-756VF", and "UH-814N" manufactured by ADEKA Corporation, "Primal RM-8W", "Primal RM-825", "Primal RM-2020NPR", "Primal RM-12W", and "Primal SCT-275" manufactured by Rohm and Haas Corporation, and "SN Thickener 612", "SN Thickener 621N", "SN Thickener 625N", "SN Thickener 627N", and "SN Thickener 660T" manufactured by San Nopco.
[0077] The content of the associative thickener (X3) in the water-based base coating material (X) is preferably within a range of 0.1 to 5 parts by mass, more preferably within a range of 0.2 to 4 parts by mass, and even more preferably within a range of 0.3 to 3 parts by mass, based on 100 parts by mass of the resin solid content in the water-based base coating material (X).
[0078] The water-based base coating material (X) may further contain, as necessary, resins other than the hydroxyl-containing acrylic resin particles (X1) and the hydroxyl-containing acrylic resin particles (X2), curing agents, pigments, organic solvents, curing catalysts, dispersants, anti-settling agents, defoamers, thickeners other than the associative thickener (X3), ultraviolet absorbers, light stabilizers, surface conditioners, etc.
[0079] Examples of resins other than the hydroxyl-containing acrylic resin particles (X1) and the hydroxyl-containing acrylic resin particles (X2) include acrylic resins other than the hydroxyl-containing acrylic resin particles (X1) and the hydroxyl-containing acrylic resin particles (X2), polyester resins, polyurethane resins, and the like.
[0080] Examples of the curing agent include amino resins, polyisocyanate compounds, and blocked polyisocyanate compounds.
[0081] Examples of the pigment include color pigments, extender pigments, luster pigments, etc. The pigments may be used alone or in combination of two or more kinds.
[0082] When the water-based base coating material (X) contains the above-mentioned pigment, the blending amount of the pigment is preferably within the range of 1 to 50 parts by mass, more preferably within the range of 2 to 40 parts by mass, and even more preferably within the range of 3 to 30 parts by mass, based on 100 parts by mass of the resin solid content in the water-based base coating material (X).
[0083] Examples of the color pigment include titanium oxide, zinc oxide, carbon black, molybdenum red, Prussian blue, cobalt blue, azo pigments, phthalocyanine pigments, quinacridone pigments, isoindoline pigments, threne pigments, perylene pigments, dioxazine pigments, and diketopyrrolopyrrole pigments.
[0084] When the water-based base coating material (X) contains the above-mentioned coloring pigment, the amount of the coloring pigment is preferably within the range of 0.1 to 30 parts by mass, more preferably within the range of 0.5 to 20 parts by mass, and even more preferably within the range of 1 to 10 parts by mass, based on 100 parts by mass of the resin solid content in the water-based base coating material (X).
[0085] Examples of the extender pigment include barium sulfate, talc, clay, kaolin, barium carbonate, calcium carbonate, silica, and alumina white.
[0086] When the water-based base coating material (X) contains the above-mentioned body pigment, the blending amount of the body pigment is preferably within the range of 0.1 to 30 parts by mass, more preferably within the range of 0.5 to 20 parts by mass, and even more preferably within the range of 1 to 10 parts by mass, based on 100 parts by mass of the resin solid content in the water-based base coating material (X).
[0087] Examples of the luster pigment include aluminum (including vapor-deposited aluminum), copper, zinc, brass, nickel, glass flakes, aluminum oxide, mica, aluminum oxide coated with titanium oxide and / or iron oxide, and mica coated with titanium oxide and / or iron oxide. Among them, it is preferable to use an aluminum pigment. Aluminum pigments include non-leafing aluminum pigments and leafing aluminum pigments, and either can be used.
[0088] The above-mentioned luster pigment is preferably in the form of a flake, and the luster pigment suitably has a longitudinal dimension in the range of 1 to 100 μm, particularly 5 to 40 μm, and a thickness in the range of 0.001 to 5 μm, particularly 0.01 to 2 μm.
[0089] When the water-based base coating material (X) contains the above-mentioned luster pigment, the amount of the luster pigment is preferably within the range of 0.1 to 30 parts by mass, more preferably within the range of 0.5 to 20 parts by mass, and even more preferably within the range of 1 to 10 parts by mass, based on 100 parts by mass of the resin solid content in the water-based base coating material (X).
[0090] Examples of the organic solvent include ketone-based solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ester-based solvents such as ethyl acetate, butyl acetate, methyl benzoate, ethyl ethoxypropionate, ethyl propionate, and methyl propionate; alcohol-based solvents such as isopropanol, n-butanol, isobutanol, and 2-ethylhexanol; ether-based solvents such as tetrahydrofuran, dioxane, and dimethoxyethane; glycol ether-based solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate; aromatic hydrocarbon-based solvents, and aliphatic hydrocarbon-based solvents.
[0091] Examples of thickeners other than the associative thickener (X3) include alkali swelling thickeners.
[0092] When using the water-based base paint (X), it can be diluted by adding water and / or an organic solvent, etc. as necessary, and adjusted to an appropriate viscosity before use. The appropriate viscosity varies depending on the paint composition, but it is preferable to adjust the viscosity, for example, using water and / or an organic solvent, appropriately so that the viscosity is within the range of 2000 to 5000 mPa·s when measured using a B-type viscometer at 20°C and a rotation speed of 6 rpm.
[0093] The coating method of the water-based base coating material (X) can be a normal coating method commonly used in the art. For example, the coating method can be a coating method using a brush or a coating machine. Among them, the coating method using a coating machine is preferred. For example, the coating machine is preferably an airless spray coating machine, an air spray coating machine, or a rotary atomizing electrostatic coating machine such as a paint cassette type, and the rotary atomizing electrostatic coating machine is particularly preferred. By using the above-mentioned coating material and coating method, an uncured base coating film having a good coating appearance can be obtained.
[0094] The base coating film preferably has a cured thickness of 5 to 15 μm, particularly preferably within the range of 7 to 12 μm.
[0095] Process (4) Step (4) of the present invention is a step of applying a glittering pigment dispersion (Y) onto the uncured base coating film to form an uncured glittering coating film. [Glitter pigment dispersion (Y)] In this specification, the term "glitter pigment dispersion (Y)" refers to an aqueous paint containing a scaly aluminum pigment (Y1), a cellulose-based viscosity modifier (Y2), a surface modifier (Y3) and water, and having a solids content within the range of 2 to 6 mass %, which is used to impart glitter.
[0096] Examples of the scaly aluminum pigment (Y1) include aluminum flake pigments and vapor-deposited aluminum flake pigments.
[0097] Aluminum flake pigments are generally produced by pulverizing and grinding aluminum in a ball mill or an attritor mill in the presence of a grinding medium using a grinding aid. As the grinding aid in the production process of the aluminum flake pigment, higher fatty acids such as oleic acid, stearic acid, isostearic acid, lauric acid, palmitic acid, myristic acid, etc., as well as aliphatic amines, aliphatic amides, and aliphatic alcohols are used. As the grinding medium, an aliphatic hydrocarbon such as mineral spirits is used.
[0098] The above aluminum flake pigments can be roughly divided into leafing type and non-leafing type depending on the type of grinding aid. In the glitter pigment dispersion (Y), it is preferable to use a non-leafing type scaly aluminum pigment from the viewpoint of obtaining a multi-layer coating film with excellent glitter. As the non-leafing type scaly aluminum pigment, those with no particular surface treatment can be used, but those with a resin-coated surface, those with a silica treatment, and those with a phosphoric acid, molybdic acid, or a silane coupling agent can also be used. Those with one of the above various surface treatments can be used, but those with multiple types of treatments can also be used.
[0099] The vapor-deposited aluminum flake pigment can be obtained by depositing an aluminum film on a base substrate, peeling off the base substrate, and then pulverizing the vapor-deposited aluminum film. Examples of the substrate include films.
[0100] Examples of commercially available products that can be used as the vapor-deposited aluminum flake pigment include the "METALURE" series (product name, manufactured by Ecart), the "Hydroshine WS" series (product name, manufactured by Ecart), the "Decomet" series (product name, manufactured by Schlenk), and the "Metasheen" series (product name, manufactured by BASF).
[0101] The content of the scaly aluminum pigment (Y1) is preferably 30 to 80 parts by mass, and more preferably 40 to 70 parts by mass, based on 100 parts by mass of the solid content in the glittering pigment dispersion (Y).
[0102] Examples of the cellulose-based viscosity modifier (Y2) include carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, cellulose nanofiber, and cellulose nanocrystal, and among these, it is preferable to use cellulose nanofiber.
[0103] The cellulose nanofibers have a number average fiber diameter in the range of preferably 2 to 500 nm, more preferably 2 to 250 nm, and even more preferably 2 to 150 nm, and a number average fiber length in the range of preferably 0.1 to 20 μm, more preferably 0.1 to 15 μm, and even more preferably 0.1 to 10 μm.
[0104] The number average fiber diameter and number average fiber length are measured and calculated from images obtained by, for example, dispersing a sample of cellulose nanofibers diluted with water, casting the sample on a carbon film-coated grid that has been hydrophilized, and observing the result with a transmission electron microscope (TEM).
[0105] The cellulose nanofibers can be obtained by defibrating a cellulose raw material and stabilizing it in water. Here, the cellulose raw material refers to various forms of materials mainly made of cellulose, and specific examples include pulp (wood pulp, pulp derived from herbs such as jute, Manila hemp, and kenaf, etc.); natural cellulose such as cellulose produced by microorganisms; regenerated cellulose spun after dissolving cellulose in some solvent such as cuprammonium solution or morpholine derivative; and fine cellulose obtained by depolymerizing cellulose by subjecting the cellulose raw material to hydrolysis, alkali hydrolysis, enzymatic decomposition, explosion treatment, mechanical treatment such as vibration ball mill, etc.
[0106] Anion-modified cellulose nanofibers can also be used as the cellulose nanofibers. Examples of anion-modified cellulose nanofibers include carboxylated cellulose nanofibers, carboxylmethylated cellulose nanofibers, sulfonic acid group-containing cellulose nanofibers, and phosphoric acid group-containing cellulose nanofibers. The anion-modified cellulose nanofibers can be obtained, for example, by introducing functional groups such as carboxyl groups and carboxylmethyl groups into a cellulose raw material by a known method, washing the resulting modified cellulose to prepare a dispersion of the modified cellulose, and defibrating the dispersion. The carboxylated cellulose is also called oxidized cellulose.
[0107] The oxidized cellulose can be obtained, for example, by oxidizing the cellulose raw material in water with an oxidizing agent in the presence of a compound selected from the group consisting of N-oxyl compounds, bromides, and iodides, or mixtures thereof.
[0108] Commercially available products of the cellulose nanofibers include, for example, LeoCrysta (registered trademark) manufactured by Daiichi Kogyo Seiyaku Co., Ltd. and AuroVisco (registered trademark) manufactured by Oji Holdings Corporation.
[0109] The content of the cellulose-based viscosity modifier (Y2) is preferably from 5 to 30 parts by mass, and more preferably from 7 to 20 parts by mass, based on 100 parts by mass of the solid content in the glittering pigment dispersion (Y).
[0110] Examples of the surface conditioner (Y3) include silicone-based surface conditioners, acrylic-based surface conditioners, vinyl-based surface conditioners, fluorine-based surface conditioners, and acetylene diol-based surface conditioners, and among these, acetylene diol-based surface conditioners are preferred.
[0111] Examples of commercially available surface conditioners (Y3) include the Dynol series, Surfynol series, and Tego series manufactured by Evonik Industries, the BYK series manufactured by BYK-Chemie, the Granol series and Polyflow series manufactured by Kyoeisha Chemical Co., Ltd., and the Disparlon series manufactured by Kusumoto Chemical Industries, Ltd.
[0112] The content of the surface conditioner (Y3) is preferably from 2 to 15 parts by mass, and more preferably from 4 to 10 parts by mass, based on 100 parts by mass of the solid content in the brilliant pigment dispersion (Y).
[0113] The solid content of the brilliant pigment dispersion (Y) is within the range of 2 to 6 mass %. By having the solid content within the range of 2 to 6 mass %, a multilayer coating film with excellent brilliant properties can be obtained.
[0114] The brilliant pigment dispersion (Y) may further contain, as necessary, a resin, a curing agent, a brilliant pigment other than the scaly aluminum pigment (Y1), a coloring pigment, an extender pigment, an organic solvent, a viscosity modifier other than the cellulose-based viscosity modifier (Y2), a pigment dispersant, a pigment derivative, an anti-settling agent, an antifoaming agent, an ultraviolet absorber, a light stabilizer, and the like.
[0115] Examples of the resin include acrylic resin, polyester resin, and urethane resin.
[0116] Examples of the curing agent include amino resins, polyisocyanate compounds, and blocked polyisocyanate compounds.
[0117] Examples of the color pigment include titanium oxide, zinc oxide, carbon black, molybdenum red, Prussian blue, cobalt blue, azo pigments, phthalocyanine pigments, quinacridone pigments, isoindoline pigments, threne pigments, perylene pigments, dioxazine pigments, and diketopyrrolopyrrole pigments.
[0118] When the brilliant pigment dispersion (Y) contains the above-mentioned coloring pigment, the amount of the coloring pigment is preferably within the range of 0.1 to 10 parts by mass, more preferably within the range of 0.2 to 5 parts by mass, and even more preferably within the range of 0.3 to 3 parts by mass, based on 100 parts by mass of the solid content in the brilliant pigment dispersion (Y).
[0119] Examples of the extender pigment include barium sulfate, talc, clay, kaolin, barium carbonate, calcium carbonate, silica, and alumina white.
[0120] When the brilliant pigment dispersion (Y) contains the above-mentioned body pigment, the blending amount of the body pigment is preferably within the range of 0.1 to 10 parts by mass, more preferably within the range of 0.2 to 5 parts by mass, and even more preferably within the range of 0.3 to 3 parts by mass, based on 100 parts by mass of the solid content in the brilliant pigment dispersion (Y).
[0121] Examples of the organic solvent include ketone-based solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ester-based solvents such as ethyl acetate, butyl acetate, methyl benzoate, ethyl ethoxypropionate, ethyl propionate, and methyl propionate; alcohol-based solvents such as isopropanol, n-butanol, isobutanol, and 2-ethylhexanol; ether-based solvents such as tetrahydrofuran, dioxane, and dimethoxyethane; glycol ether-based solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate; aromatic hydrocarbon-based solvents, and aliphatic hydrocarbon-based solvents.
[0122] Examples of the viscosity modifier other than the cellulose-based viscosity modifier (Y2) include polyacrylic acid-based viscosity modifiers, polyamide-based viscosity modifiers, mineral-based viscosity modifiers, and polysaccharide-based viscosity modifiers.
[0123] The coating method of the glitter pigment dispersion (Y) can be a normal coating method commonly used in the art. For example, the coating method can be a coating method using a brush or a coating machine. Among them, the coating method using a coating machine is preferred. For example, the coating machine is preferably an airless spray coating machine, an air spray coating machine, or a rotary atomizing electrostatic coating machine such as a paint cassette type, and the rotary atomizing electrostatic coating machine is particularly preferred. By using the above-mentioned paint and coating method, an uncured glitter coating film having a good coating appearance can be obtained.
[0124] The glossy coating film obtained from the glossy pigment dispersion (Y) has a cured film thickness of 0.5 to 1.5 μm. By making the glossy coating film have a cured film thickness of 0.5 to 1.5 μm, a multi-layer coating film having excellent glossiness can be obtained.
[0125] Process (5) Step (5) of the present invention is a preheating step in which the uncured base coating film and the uncured glittering coating film are preheated.
[0126] The temperature for the preheating treatment is preferably within a range of 60 to 100° C., and more preferably within a range of 70 to 90° C. The time for the preheating treatment is preferably 1 to 5 minutes.
[0127] Process (6) The step (6) of the present invention is a step of applying a clear coating (Z) onto the preheat-treated glossy coating film to form an uncured clear coating film. [Clear paint (Z)] In this specification, "clear coating (Z)" is a transparent coating used to protect the primer coating, the base coating, and the gloss coating.
[0128] The clear coating material (Z) used in this step is preferably a coating material commonly used in the art, and contains a base resin, a curing agent, and a medium consisting of water or an organic solvent. Here, the base resin and curing agent may be any known compound commonly used in the art. Examples of the base resin include carboxyl group-containing acrylic resin, epoxy group-containing acrylic resin, and hydroxyl group-containing acrylic resin. Examples of the curing agent may include melamine resin, urea resin, polyisocyanate compound, blocked polyisocyanate compound, and the like.
[0129] Examples of organic solvents include aliphatic hydrocarbons such as hexane and heptane, aromatic hydrocarbons such as xylene and toluene, and alicyclic hydrocarbons; esters such as ethyl acetate and butyl acetate; ethers such as ethylene glycol monomethyl ether; alcohols such as ethanol, propanol, and 2-ethylhexyl alcohol; ketones such as methyl ethyl ketone and methyl isobutyl ketone; and amides. Examples of organic solvents containing aromatic hydrocarbons include Swazol 310 and Swazol 1000 (manufactured by Cosmo Oil Co., Ltd.).
[0130] The clear coating material (Z) used in the method of the present invention may contain, in addition to the above-mentioned components, coloring pigments, luster pigments, extender pigments, ultraviolet absorbers, defoamers, thickeners, rust inhibitors, surface conditioners, etc., as desired.
[0131] By applying the clear coating material (Z) having the above-mentioned composition, it is possible to obtain a clear coating film having a dry film thickness sufficient for protecting the base coating film and the glossy coating film, and also having excellent surface smoothness.
[0132] The coating method of the clear coating material (Z) can be a normal coating method commonly used in the art. For example, the coating method can be a coating method using a brush or a coating machine. Among them, the coating method using a coating machine is preferred. For example, the coating machine is preferably an airless spray coating machine, an air spray coating machine, or a rotary atomizing electrostatic coating machine such as a paint cassette type, and the rotary atomizing electrostatic coating machine is particularly preferred. By using the above coating material and coating method, an uncured clear coating film having a good coating appearance can be obtained.
[0133] The cured film thickness of the clear coating film obtained from the clear coating material (Z) is preferably 15 to 40 μm, particularly preferably 20 to 30 μm, from the viewpoint of obtaining a multi-layer coating film excellent in finished appearance and brilliance.
[0134] Process (7) Step (7) of the present invention is a step of simultaneously curing the preheat-treated primer coating film, base coating film, and glitter coating film, as well as the uncured clear coating film, by heating them at a temperature in the range of 110 to 130°C.
[0135] The heating can be, for example, hot air heating, infrared heating, high frequency heating, etc., and the heating temperature is within the range of 110 to 130° C. The heating time is preferably 10 to 60 minutes, more preferably 15 to 40 minutes. EXAMPLES
[0136] The present invention will be described in more detail below with reference to Production Examples, Examples, and Comparative Examples. Note that these Production Examples, Examples, and Comparative Examples are merely illustrative and are not intended to limit the scope of the present invention. In the Production Examples, Examples, and Comparative Examples, "parts" and "%" are based on mass unless otherwise specified. The film thickness of the coating film is based on the cured coating film.
[0137] Production of hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90-100 mgKOH / g Manufacturing Example 1 A reaction vessel equipped with a thermometer, thermostat, stirring device, reflux condenser, nitrogen inlet tube, and dropping device was charged with 128 parts of deionized water and 2 parts of "ADEKA REASOAP SR-1025" (product name, manufactured by ADEKA, emulsifier, active ingredient 25%), stirred and mixed in a nitrogen stream, and heated to 80°C.
[0138] Next, 1% of the total amount of the below-mentioned core monomer emulsion and 5.3 parts of a 6% ammonium persulfate aqueous solution were introduced into the reaction vessel and held at 80°C for 15 minutes. After that, the remaining part of the core monomer emulsion was dropped into the reaction vessel held at the same temperature over 3 hours, and aging was carried out for 1 hour after the end of the dropwise addition. Next, the below-mentioned shell monomer emulsion was dropped into the reaction vessel over 1 hour, and after aging for 1 hour, the reaction vessel was cooled to 30°C while gradually adding 40 parts of a 5% 2-(dimethylamino)ethanol aqueous solution, and discharged while filtering with a 100 mesh nylon cloth, to obtain hydroxyl-containing acrylic resin particles (X1-1) having a core-shell structure with an average particle size of 100 nm and an acid value of the shell with a solid content of 30% of 90 to 100 mgKOH / g. The obtained hydroxyl-containing acrylic resin particles (X1-1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g had a shell acid value of 96 mgKOH / g.
[0139] Core monomer emulsion: 40 parts of deionized water, 2.8 parts of "ADEKA REASOAP SR-1025", 2.1 parts of methylene bisacrylamide, 22.9 parts of styrene, 25 parts of methyl methacrylate, 15 parts of ethyl acrylate, and 5 parts of n-butyl acrylate were mixed and stirred to obtain a core monomer emulsion.
[0140] Shell monomer emulsion: 17 parts of deionized water, 1.2 parts of "ADEKA REASOAP SR-1025", 0.03 parts of ammonium persulfate, 2.8 parts of styrene, 2.2 parts of 2-hydroxyethyl acrylate, 4.4 parts of methacrylic acid, 6 parts of methyl methacrylate, 1.8 parts of ethyl acrylate, and 12.8 parts of n-butyl acrylate were mixed and stirred to obtain a shell monomer emulsion.
[0141] Production of hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110-120 mgKOH / g Manufacturing Example 2 A reaction vessel equipped with a thermometer, thermostat, stirring device, reflux condenser, nitrogen inlet tube, and dropping device was charged with 128 parts of deionized water and 2 parts of "ADEKA REASOAP SR-1025" (product name, manufactured by ADEKA, emulsifier, active ingredient 25%), stirred and mixed in a nitrogen stream, and heated to 80°C.
[0142] Next, 1% of the total amount of the below-mentioned core monomer emulsion and 5.3 parts of a 6% ammonium persulfate aqueous solution were introduced into the reaction vessel and held at 80°C for 15 minutes. After that, the remaining part of the core monomer emulsion was dropped into the reaction vessel held at the same temperature over 3 hours, and aging was carried out for 1 hour after the end of the dropwise addition. Next, the below-mentioned shell monomer emulsion was dropped into the reaction vessel over 1 hour, and after aging for 1 hour, the reaction vessel was cooled to 30°C while gradually adding 40 parts of a 5% 2-(dimethylamino)ethanol aqueous solution, and discharged while filtering with a 100 mesh nylon cloth, to obtain hydroxyl-containing acrylic resin particles (X2-1) having a core-shell structure with an average particle size of 100 nm and an acid value of the shell with a solid content of 30% of 110 to 120 mgKOH / g. The obtained hydroxyl-containing acrylic resin particles (X2-1) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g had a shell acid value of 115 mgKOH / g.
[0143] Core monomer emulsion: 40 parts of deionized water, 2.8 parts of "ADEKA REASOAP SR-1025", 2.1 parts of methylene bisacrylamide, 22.9 parts of styrene, 15 parts of methyl methacrylate, 15 parts of ethyl acrylate, and 15 parts of n-butyl acrylate were mixed and stirred to obtain a core monomer emulsion.
[0144] Shell monomer emulsion: A monomer emulsion for the shell portion was obtained by mixing and stirring 17 parts of deionized water, 1.2 parts of "ADEKA REASOAP SR-1025", 0.03 parts of ammonium persulfate, 2.8 parts of styrene, 2.2 parts of 2-hydroxyethyl acrylate, 5.3 parts of methacrylic acid, 10 parts of methyl methacrylate, 3.7 parts of ethyl acrylate, and 6 parts of n-butyl acrylate.
[0145] Manufacture of other hydroxyl-containing acrylic resin particles (C) Production Example 3 A reaction vessel equipped with a thermometer, thermostat, stirring device, reflux condenser, nitrogen inlet tube, and dropping device was charged with 128 parts of deionized water and 2 parts of "ADEKA REASOAP SR-1025" (product name, manufactured by ADEKA, emulsifier, active ingredient 25%), stirred and mixed in a nitrogen stream, and heated to 80°C.
[0146] Next, 1% of the total amount of the below-mentioned core monomer emulsion and 5.3 parts of a 6% aqueous solution of ammonium persulfate were introduced into the reaction vessel and held at 80°C for 15 minutes. After that, the remaining part of the core monomer emulsion was dropped into the reaction vessel held at the same temperature over 3 hours, and aging was performed for 1 hour after the end of the dropwise addition. Next, the below-mentioned shell monomer emulsion was dropped into the reaction vessel over 1 hour, and after aging for 1 hour, the reaction vessel was cooled to 30°C while gradually adding 40 parts of a 5% aqueous solution of 2-(dimethylamino)ethanol to the reaction vessel, and the mixture was discharged while filtering through a 100-mesh nylon cloth, to obtain hydroxyl-containing acrylic resin particles (C-1) having a core-shell structure with an average particle size of 100 nm and a solid content of 30%. The obtained hydroxyl-containing acrylic resin particles (C-1) having a core-shell structure had a shell acid value of 85 mgKOH / g.
[0147] Core monomer emulsion: 40 parts of deionized water, 2.8 parts of "ADEKA REASOAP SR-1025", 2.1 parts of methylene bisacrylamide, 22.9 parts of styrene, 25 parts of methyl methacrylate, 15 parts of ethyl acrylate, and 5 parts of n-butyl acrylate were mixed and stirred to obtain a core monomer emulsion.
[0148] Shell monomer emulsion: 17 parts of deionized water, 1.2 parts of "ADEKA REASOAP SR-1025", 0.03 parts of ammonium persulfate, 3.3 parts of styrene, 2.2 parts of 2-hydroxyethyl acrylate, 3.9 parts of methacrylic acid, 6 parts of methyl methacrylate, 1.8 parts of ethyl acrylate, and 12.8 parts of n-butyl acrylate were mixed and stirred to obtain a shell monomer emulsion.
[0149] Production Example 4 A reaction vessel equipped with a thermometer, thermostat, stirring device, reflux condenser, nitrogen inlet tube, and dropping device was charged with 128 parts of deionized water and 2 parts of "ADEKA REASOAP SR-1025" (product name, manufactured by ADEKA, emulsifier, active ingredient 25%), stirred and mixed in a nitrogen stream, and heated to 80°C.
[0150] Next, 1% of the total amount of the below-mentioned core monomer emulsion and 5.3 parts of a 6% ammonium persulfate aqueous solution were introduced into the reaction vessel and held at 80°C for 15 minutes. After that, the remaining part of the core monomer emulsion was dropped into the reaction vessel held at the same temperature over 3 hours, and aging was performed for 1 hour after the end of the dropwise addition. Next, the below-mentioned shell monomer emulsion was dropped into the reaction vessel over 1 hour, and after aging for 1 hour, the reaction vessel was cooled to 30°C while gradually adding 40 parts of a 5% 2-(dimethylamino)ethanol aqueous solution, and discharged while filtering with a 100-mesh nylon cloth, to obtain hydroxyl-containing acrylic resin particles (C-2) having a core-shell structure with an average particle size of 100 nm and a solid content of 30%. The obtained hydroxyl-containing acrylic resin particles (C-2) having a core-shell structure had a shell acid value of 106 mgKOH / g.
[0151] Core monomer emulsion: 40 parts of deionized water, 2.8 parts of "ADEKA REASOAP SR-1025", 2.1 parts of methylene bisacrylamide, 22.9 parts of styrene, 18 parts of methyl methacrylate, 15 parts of ethyl acrylate, and 12 parts of n-butyl acrylate were mixed and stirred to obtain a core monomer emulsion.
[0152] Shell monomer emulsion: A monomer emulsion for the shell portion was obtained by mixing and stirring 17 parts of deionized water, 1.2 parts of "ADEKA REASOAP SR-1025", 0.03 parts of ammonium persulfate, 3.3 parts of styrene, 2.2 parts of 2-hydroxyethyl acrylate, 4.9 parts of methacrylic acid, 8.8 parts of methyl methacrylate, 1.8 parts of ethyl acrylate, and 9 parts of n-butyl acrylate.
[0153] Production Example 5 A reaction vessel equipped with a thermometer, thermostat, stirring device, reflux condenser, nitrogen inlet tube, and dropping device was charged with 128 parts of deionized water and 2 parts of "ADEKA REASOAP SR-1025" (product name, manufactured by ADEKA, emulsifier, active ingredient 25%), stirred and mixed in a nitrogen stream, and heated to 80°C.
[0154] Next, 1% of the total amount of the monomer emulsion for the core part described below and 5.3 parts of a 6% aqueous solution of ammonium persulfate were introduced into the reaction vessel and held at 80°C for 15 minutes. After that, the remaining part of the monomer emulsion for the core part was dropped into the reaction vessel held at the same temperature over 3 hours, and aging was performed for 1 hour after the end of the dropwise addition. Next, the monomer emulsion for the shell part described below was dropped into the reaction vessel over 1 hour, and after aging for 1 hour, the reaction vessel was cooled to 30°C while gradually adding 40 parts of a 5% aqueous solution of 2-(dimethylamino)ethanol to the reaction vessel, and the mixture was discharged while filtering through a 100-mesh nylon cloth to obtain hydroxyl-containing acrylic resin particles (C-3) having a core-shell structure with an average particle size of 100 nm and a solid content of 30%. The obtained hydroxyl-containing acrylic resin particles (C-3) having a core-shell structure had a shell acid value of 126 mgKOH / g.
[0155] Core monomer emulsion: 40 parts of deionized water, 2.8 parts of "ADEKA REASOAP SR-1025", 2.1 parts of methylene bisacrylamide, 22.9 parts of styrene, 12 parts of methyl methacrylate, 18 parts of ethyl acrylate, and 12 parts of n-butyl acrylate were mixed and stirred to obtain a core monomer emulsion.
[0156] Shell monomer emulsion: A monomer emulsion for the shell portion was obtained by mixing and stirring 17 parts of deionized water, 1.2 parts of "ADEKA REASOAP SR-1025", 0.03 parts of ammonium persulfate, 2.8 parts of styrene, 2.2 parts of 2-hydroxyethyl acrylate, 5.8 parts of methacrylic acid, 10 parts of methyl methacrylate, 3.2 parts of ethyl acrylate, and 6 parts of n-butyl acrylate.
[0157] Preparation of hydroxyl-containing acrylic resin solution Production Example 6 A reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube and a dropping device was charged with 35 parts of propylene glycol monopropyl ether and heated to 85°C. A mixture of 30 parts of methyl methacrylate, 20 parts of 2-ethylhexyl acrylate, 29 parts of n-butyl acrylate, 15 parts of 2-hydroxyethyl acrylate, 6 parts of acrylic acid, 15 parts of propylene glycol monopropyl ether and 2.3 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was added dropwise over 4 hours, and the mixture was aged for 1 hour after the end of the dropwise addition. Then, a mixture of 10 parts of propylene glycol monopropyl ether and 1 part of 2,2'-azobis(2,4-dimethylvaleronitrile) was added dropwise over 1 hour, and the mixture was aged for 1 hour after the end of the dropwise addition. 7.4 parts of diethanolamine were added to obtain a hydroxyl group-containing acrylic resin solution (R-1) with a solid content of 55%. The resulting hydroxyl-containing acrylic resin solution (R-1) had an acid value of 47 mgKOH / g, a hydroxyl value of 72 mgKOH / g, and a weight average molecular weight of 58,000.
[0158] Preparation of acrylic resin solution having hydroxyl and phosphate groups Production Example 7 A mixed solvent of 27.5 parts of methoxypropanol and 27.5 parts of isobutanol was placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube and a dropping device, and heated to 110 ° C., and 121.5 parts of a mixture consisting of 25.0 parts of styrene, 27.5 parts of n-butyl methacrylate, 20.0 parts of "isostearyl acrylate" (trade name, manufactured by Osaka Organic Chemical Industry Co., Ltd., branched higher alkyl acrylate), 7.5 parts of 4-hydroxybutyl acrylate, 15.0 parts of the following phosphoric acid group-containing polymerizable monomer, 12.5 parts of 2-methacryloyloxyethyl acid phosphate, 10.0 parts of isobutanol, and 4.0 parts of t-butyl peroxy octanoate was added to the mixed solvent over 4 hours, and a mixture consisting of 0.5 parts of t-butyl peroxy octanoate and 20.0 parts of isopropanol was added dropwise for 1 hour. After that, the mixture was stirred and aged for 1 hour to obtain an acrylic resin solution (R-2) having a solid content of 50% and having hydroxyl and phosphate groups. The obtained acrylic resin solution (R-2) having hydroxyl and phosphate groups had an acid value of 83 mgKOH / g, a hydroxyl value of 29 mgKOH / g, and a weight average molecular weight of 10,000.
[0159] Phosphate-containing polymerizable monomer: 57.5 parts of monobutyl phosphate and 41.0 parts of isobutanol were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirring device, a reflux condenser, a nitrogen inlet tube and a dropping device, and the temperature was raised to 90°C. After that, 42.5 parts of glycidyl methacrylate were dropped over 2 hours, and the mixture was further stirred and aged for 1 hour. Then, 59.0 parts of isopropanol were added to obtain a phosphoric acid-containing polymerizable monomer solution with a solid content concentration of 50%. The acid value of the obtained monomer was 285 mgKOH / g.
[0160] Preparation of hydroxyl-containing polyester resin Production Example 8 In a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, and a water separator, 109 parts of trimethylolpropane, 141 parts of 1,6-hexanediol, 126 parts of 1,2-cyclohexanedicarboxylic anhydride, and 120 parts of adipic acid were charged, and the temperature was raised from 160°C to 230°C over 3 hours, and then condensation reaction was carried out at 230°C for 4 hours. Next, in order to introduce carboxyl groups into the obtained condensation reaction product, 38.3 parts of trimellitic anhydride were added, and the reaction was carried out at 170°C for 30 minutes, and then diluted with 2-ethyl-1-hexanol to obtain a hydroxyl group-containing polyester resin solution (R-3) with a solid content of 70%. The obtained hydroxyl group-containing polyester resin (R-3) had an acid value of 46 mgKOH / g, a hydroxyl value of 150 mgKOH / g, and a number average molecular weight of 1,400.
[0161] Manufacture of blocked polyisocyanate compounds Production Example 9 In a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux condenser, a nitrogen inlet tube, a dropping device and a simple trap for removing solvent, 360 parts of "Sumidur N-3300" (trade name, manufactured by Sumika Bayer Urethane Co., Ltd., Sumidur is a registered trademark, isocyanurate structure-containing polyisocyanate derived from hexamethylene diisocyanate, solid content about 100%, isocyanate group content 21.8%), 60 parts of "Uniox M-550" (trade name, manufactured by NOF Corp., Uniox is a registered trademark, polyethylene glycol monomethyl ether, average molecular weight about 550) and 0.2 parts of 2,6-di-tert-butyl-4-methylphenol were charged, mixed well and heated at 130 ° C. for 3 hours under a nitrogen stream. Next, 110 parts of ethyl acetate and 252 parts of diisopropyl malonate were charged, and 3 parts of a 28% methanol solution of sodium methoxide were added while stirring under a nitrogen stream, and the mixture was stirred at 65 ° C. for 8 hours. The amount of isocyanate in the obtained resin solution was 0.12 mol / kg. 683 parts of 4-methyl-2-pentanol was added thereto, and the solvent was distilled off under reduced pressure conditions for 3 hours while maintaining the temperature of the system at 80 to 85°C, to obtain 1010 parts of a blocked polyisocyanate compound (R-4). 95 parts of isopropanol was contained in the simple solvent removal trap. The solid content concentration of the obtained blocked polyisocyanate compound (R-4) was 60%.
[0162] Manufacturing of color pigment dispersions Manufacturing Example 10 5.5 parts of the hydroxyl-containing acrylic resin solution (R-1) obtained in Production Example 6 (resin solid content: 3 parts), 1 part of "Carbon MA-100" (trade name, Mitsubishi Chemical Corporation, carbon black pigment), and 20 parts of deionized water were mixed, adjusted to pH 8.2 with 2-(dimethylamino)ethanol, and then dispersed for 30 minutes with a paint shaker to obtain a colored pigment dispersion (P-1).
[0163] Manufacture of extender pigment dispersions Manufacturing Example 11 5.5 parts (resin solids: 3 parts) of the hydroxyl-containing acrylic resin solution (R-1) obtained in Production Example 6, 10 parts of "Varifine BF-20" (product name, Sakai Chemical Industry Co., Ltd., barium sulfate pigment), 0.6 parts (solids: 0.3 parts) of "Surfynol 104A" (product name, Air Products Co., Ltd., defoamer, solids: 50%), and 20 parts of deionized water were mixed and dispersed for 1 hour using a paint shaker to obtain an extender pigment dispersion (P-2).
[0164] Manufacture of glitter pigment dispersions Manufacturing Example 12 In a stirring mixing vessel, 8 parts (solid content 6 parts) of "ALPASTE TCR2060" (product name, manufactured by Toyo Aluminum, aluminum pigment paste, aluminum content 75%), 35.0 parts of 2-ethyl-1-hexanol, and 8 parts (solid content 4 parts) of the acrylic resin solution having hydroxyl groups and phosphate groups (R-2) obtained in Production Example 7 were uniformly mixed to obtain a brilliant pigment dispersion (P-3).
[0165] Manufacture of water-based paint (X) Manufacturing Example 13 60 parts (18 parts solids) of hydroxyl-containing acrylic resin particles (X1-1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g obtained in Production Example 1, 40 parts (12 parts solids) of hydroxyl-containing acrylic resin particles (X2-1) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g obtained in Production Example 2, 42.9 parts (30 parts solids) of polyester resin solution (R-4) obtained in Production Example 8, 25 parts (15 parts solids) of blocked polyisocyanate compound (R-5) obtained in Production Example 9, 26.5 parts of color pigment dispersion (P-1) obtained in Production Example 10 36.1 parts of the extender pigment dispersion (P-2) obtained in Production Example 11, 51 parts of the glittering pigment dispersion (P-3) obtained in Production Example 12, 21.4 parts (15 parts solids) of melamine resin (weight average molecular weight 1,200, solids content 70%), and 5.4 parts (1.5 parts solids) of "UH-752" (trade name, ADEKA Corporation, associative thickener, solids content 28%) were mixed uniformly, and 2-(dimethylamino)ethanol and deionized water were added to obtain a water-based base paint (X-1) with a paint viscosity "B6 value" of 4000 mPa·s measured at pH 8.0, paint solids content 25%, and temperature 20°C. The B6 value is the viscosity measured with a B-type viscometer after 1 minute at a rotor rotation speed of 6 rpm, and a "digital Vismetron viscometer VDA type" (Shibaura Systems Co., Ltd.) was used as the B-type viscometer.
[0166] Manufacturing Examples 14-20 Water-based paints (X-2) to (X-8) having a pH of 8.0 were obtained in the same manner as in Production Example 13, except that the blending composition and viscosity in Production Example 13 were those shown in Table 1 below. The blending composition shown in Table 1 is based on the solid content by mass.
[0167] [Table 1]
[0168] (*1) "Primal ASE-60" (product name, Dow Chemical Company, alkali swelling thickener, solids content 28%).
[0169] Manufacture of glitter pigment dispersion (Y) Manufacturing Example 21 In a stirring and mixing vessel, acetylene diol-based surface conditioner (0.3 parts solids), "Alpaste EMR-B6360" (trade name, non-leafing aluminum flake, manufactured by Toyo Aluminum Co., Ltd., average particle diameter D50: 10.3 μm, average thickness: 0.19 μm, surface treated with silica) (1.5 parts solids), phosphoric acid group-containing cellulose nanofiber aqueous dispersion (number average fiber diameter 4 nm, phosphoric acid group introduction amount 1.50 mmol / g) (0.5 parts solids), triazine-based ultraviolet absorber (0.1 parts solids), hindered amine-based light stabilizer (0.1 parts solids), and color pigment dispersion (P-1) (0.1 parts solids) obtained in Production Example 10 were added and stirred and mixed. Next, a mixture of water / isopropyl alcohol (water / isopropyl alcohol = 6 / 1) was added to prepare a glittering pigment dispersion (Y-1) with a solid content of 4.5%. The paint viscosity "B6 value" was 1500 mPa·s.
[0170] Preparation of water-based primer paint (W) Water-based primer paint (W-1): "ASCALEX 2870CD-1 Dark Gray" (product name, manufactured by Kansai Paint Co., Ltd., acrylic resin-based water-based conductive primer paint for PP materials) was used as the water-based primer paint (W-1).
[0171] Adjustment of clear paint (Z) Clear paint (Z-1): "KINO6510" (product name, manufactured by Kansai Paint Co., Ltd., hydroxyl group / isocyanate group curing type acrylic resin / urethane resin based two-liquid organic solvent type paint) was used as the clear paint (Z-1).
[0172] Preparation of test specimens Black polypropylene was used as the plastic molded article, which was degreased and used as a coating material for testing.
[0173] (Preparation of test coated panels) Example 1 The water-based primer paint (W-1) was applied to the above test substrate using a rotary atomizing type coating machine so that the cured film thickness was 9 μm to form an uncured primer coating film, which was then left for 3 minutes and then preheated at 60°C for 3 minutes.
[0174] Next, the water-based base paint (X-1) obtained in Production Example 13 was applied onto the preheat-treated primer coating film using an ABB Robot Bell under conditions of a booth temperature of 22°C and humidity of 78% so that the dry coating film had a thickness of 10 μm to form an uncured base coating film, and was left to stand for 3 minutes.
[0175] Next, the glittering pigment dispersion (Y-1) obtained in Production Example 21 was applied onto the uncured base coating film using an ABB Robot Bell under conditions of a booth temperature of 22°C and a humidity of 78% so that the dry coating film had a thickness of 0.6 μm to form an uncured glittering coating film, which was then left for 3 minutes and then preheated at 80°C for 3 minutes.
[0176] Next, a clear coating (Z-1) was applied to the preheated glossy coating film using an ABB Robot Bell under conditions of a booth temperature of 23°C and humidity of 68% so that the dry coating film had a thickness of 25μm to form a clear coating film. After coating, the board was left at room temperature for 7 minutes, and then heated at 120°C for 30 minutes in a hot air circulation drying oven to simultaneously dry the multi-layer coating film to obtain a test panel.
[0177] Example 2 and Comparative Examples 1 to 6 Test panels were obtained in the same manner as in Example 1, except that the paints shown in Table 2 were used.
[0178] (Coating film evaluation) Each test panel obtained as described above was evaluated for the following items, and the results are shown in Table 2.
[0179] 60° mirror gloss (60° gloss) Using a multi-angle colorimeter (BYK, product name: BYK-mac i), the L* value at a light receiving angle of -15 degrees (L*-15 value) was measured. The higher the value, the better. A value of 178 or higher is considered a pass.
[0180] Finished appearance (sauce) Each test panel was visually observed, and the degree of sagging was evaluated according to the following criteria.
[0181] Pass: No sagging observed, excellent coating appearance. Fail: Dripping is observed and the coating appearance is poor.
[0182] Finished appearance (skin) Each test panel was visually observed, and the degree of skin was evaluated according to the following criteria.
[0183] Pass: The surface is good and the coating has excellent appearance. Fail: The surface is poor and the coating appearance is poor.
[0184] [Table 2]
Claims
[Claim 1] Step (1): A step of applying an aqueous primer paint (W) onto a plastic molded product to form an uncured primer coating film; Step (2): A preheating step of preheating the uncured primer coating film; Step (3): A step of applying an aqueous base coating material (X) onto the preheat-treated primer coating film to form an uncured base coating film; Step (4): A step of applying a glittering pigment dispersion (Y) onto the uncured base coating film to form an uncured glittering coating film; Step (5): A preheating step of preheating the uncured base coating film and the uncured glossy coating film; Step (6): A step of applying a clear coating material (Z) onto the preheat-treated glossy coating film to form an uncured clear coating film; Step (7): A method for forming a multilayer coating film, comprising the steps of heating the preheat-treated primer coating film, base coating film, and glitter coating film, and the uncured clear coating film at a temperature in the range of 110 to 130° C. to simultaneously cure the preheat-treated primer coating film, base coating film, and glitter coating film, and the uncured clear coating film, The aqueous base coating material (X) comprises hydroxyl-containing acrylic resin particles (X1) having a core-shell structure with a shell acid value of 90 to 100 mgKOH / g, hydroxyl-containing acrylic resin particles (X2) having a core-shell structure with a shell acid value of 110 to 120 mgKOH / g, and an associative thickener (X3), the content ratio of the hydroxyl-containing acrylic resin particles (X1) and the hydroxyl-containing acrylic resin particles (X2) is, in terms of a mass ratio of the hydroxyl-containing acrylic resin particles (X1) / the hydroxyl-containing acrylic resin particles (X2), 70 / 30 to 30 / 70; the brilliant pigment dispersion (Y) contains a scaly aluminum pigment (Y1), a cellulose-based viscosity modifier (Y2), a surface modifier (Y3) and water, and has a solid content in the range of 2 to 6 mass %, The method for forming a multilayer coating film, wherein the glossy coating film has a thickness of 0.5 to 1.5 μm after curing.
Citation Information
Patent Citations
Method of forming metallic tone glittery coating film and coated article
JP2008237939A
Method for forming multi-layer coating film
WO2018092874A1